Adsorption mechanism of silica/polymer-based 2, 6-bis(5, 6-diisohexyl-1, 2, 4-triazin-3-yl)pyridine adsorbent towards Ln(III) from nitric acid solution. Issue 9 (1st September 2016) - Ning, Shunyan; Zou, Qing; Wang, Xinpeng; Liu, Ruiqin; Wei, Yuezhou
ABSTRACT: 2, 6-Bis(5, 6-di iso hexyl-1, 2, 4-triazin-3-yl)pyridine ( iso Hexyl-BTP) is a nitrogen-donor chelating ligand which shows high extraction selectivity for minor actinides (MA) over lanthanides (Ln). We synthesized a macroporous sillica/polymer-based iso Hexyl-BTP adsorbent ( iso Hexyl-BTP/SiO2 -P) for the separation of MA(III) from Ln(III) in high-level liquid waste. The work focused on the iso Hexyl-BTP/SiO2 -P adsorption mechanism towards Ln(III) in nitric acid solution and the coordination chemistry between Ln(III) and iso Hexyl-BTP/SiO2 -P through batch adsorption experiments, extended X-ray absorption fine spectroscopy, acid-base titration and ion chromatography. It was found that both H + and NO3 − directly participated in the adsorption reaction. For the middle and heavy Ln(III), Ln( iso Hexyl-BTP/SiO2 -P)3 (NO3 )3 ·3HNO3 was supposed as the main product of the adsorption. The Ln(III)-N (Ln( iso Hexyl-BTP/SiO2 -P)3 3+ ) bond length of the first coordination layer decreased as the atomic number of Ln(III) increased, which explains the increased adsorption affinity of iso Hexyl-BTP/SiO2 -P towards middle and heavy Ln(III) in relatively high concentration nitric acid as the Ln(III) atomic number increased.